A Learning factory experimenting with adaptable production in Finnish engineering workshops - Alasoini, Tuomo (International journal of human factors in manufacturing)
This article presents an overview of the theoretical framework, methodology, and research setting of the Finnish Research Program, "Work, Culture, and Technology" being carried out in four Finnish engineering shops. The purpose of the ongoing study is to test and consolidate a new mode of operations, adaptable production, within the companies.